Cultural influences, decision making process and consumer behaviour of the Middle Class Chinese Outbound Tourist. - Bollen, Luc JJ (2010)
The research investigates the consumer behaviour of the emerging “Middle Class Mainland Chinese Outbound Tourist”. With the Chinese outbound tourism market being one of the fastest growing worldwide and poised for exponential growth in years to come, tourism industry professionals would benefit from a deeper understanding. The focus of the thesis considers which cultural influences are important in the decision making process of the Chinese middle class consumer, what are the pre-consumption, during-and post consumption behaviour traits, what influences repeat-purchases and what impact does outbound tourism has on cultural values. Further the thesis compares the research finding to consumer behaviour theories. Accelerated growth of Chinese outbound tourism started only early in the 21st century and little academic and empirical research has been done on the consumer behaviour of the Chinese middle class outbound tourist. This thesis, through market research, aims to highlight current cultural and consumption behavioural traits in order to gain better knowledge for industry professionals in understanding this major market segment.